SU JETİ İLE HAVALANDIRMA SİSTEMİNDE AĞIZLIK TİPİNİN HAVALANDIRMA PERFORMANSINA ETKİSİ - BAĞATUR, TAMER (Fırat Üniveristesi, 2000)
In this study, for the plunging water jet aeration system using inclined different nozzle types, the flow characteristics such as the bubble penetration depth, air entrainment rate, oxygen transfer factor and aeration efficiency which changed depending on the jet velocity were evaluated in an air- water system. Numerous studies were conducted with circular nozzle. The present study describe new experiments performed with different nozzle types. Three types of nozzles i.e. circular, ellipse exit nozzle and rectangle duct with rounded ends exit nozzle were examined. Experimental results showed that these two types (ellipse and rectangle duct with rounded ends exit nozzle) of jet have very different flow characterizes and entrainment patterns on free jet surface and also submerged jet region within the receiving pool (tank). More aeration performance was observed by air entrainment rate and oxygen transfer efficiency in rectangle duct with rounded ends exit nozzle. But also bubble penetration depth is less and ellipse exit nozzle is indicated a rather high quality the way bubble penetration depth. From these results, it may be said that it is appropriate to be preferred ellipse exit nozzle on aeration of the deeper and rectangle duct with rounded ends exit nozzle in the practices which are needed like bubble concentration. Key Words : Plunging water jet, aeration, nozzle type
The Effect of nozzle type on aeration performance in plunging water jet aeration system
Bu tezin, veri tabanı üzerinden yayınlanma izni bulunmamaktadır. Yayınlanma izni olmayan tezlerin basılı kopyalarına Üniversite kütüphaneniz aracılığıyla (TÜBESS üzerinden) erişebilirsiniz.
Keywords: İnşaat Mühendisliği; Civil Engineering